Status quo and influencing factors of job burnout among residents in standardized training - An, Jiale; Chang, Yu; Zhang, Xiyuan; Zhang, Minghao; Lei, Xia; Yang, MingYi; Hu, Yunfeng (Frontiers in Public Health, 2024)
BackgroundWith the continuous progress and in-depth implementation of the reform of the medical and health care system, alongside the gradual enhancement of the standardized training framework for residents, such training has become a crucial avenue for cultivating high-level clinicians and improving medical quality. However, due to various constraints and limitations in their own capabilities, residents undergoing standardized training are often susceptible to job burnout during this process. Numerous factors contribute to job burnout, which is closely associated with depression and anxiety. To promote effective standardized training and develop high-quality resident personnel, it is essential to investigate the influencing factors of job burnout and implement strategies to mitigate its occurrence.ObjectiveExplore the job burnout and its influencing factors among standardized training residents of Affiliated Hospital of Yan ‘an University, and to provide favorable basis for effective prevention of job burnout.MethodsAn online questionnaire survey was conducted among all standardized training residents at the hospital from June 2020 to September 2022. The evaluation utilized a general situation questionnaire, the Job Burnout Inventory - General Survey (MBI-GS), the Self-Rating Anxiety Scale (SAS), and the Self-Rating Depression Scale (SDS).ResultsA total of 660 valid questionnaires were collected, and 315 people had positive reaction for job burnout, and the detection rate was 47.7%. Difference in gender, marital status, whether they held practicing certificates, participated in work before training, used sleep medication, age, grade, sleep state were the influencing factors of different dimensions of job burnout. 175 people were in a state of anxiety (26.5%), while 357 (54.1%) were depressed. Pearson correlation analysis showed that anxiety and depression were highly correlated with job burnout (p < 0.01). The results of multi-factor analysis showed that sleep status, whether to take sleep AIDS, anxiety and depression were the factors affecting the dimension of emotional exhaustion (p < 0.01). Income, sleep status, anxiety and depression scores were the influencing factors of job burnout dimension (p < 0.05). Sleep status and depression score were the factors affecting the dimension of reduced sense of achievement (p < 0.05).ConclusionJob burnout is prevalent among residents undergoing standardized training, and the factors influencing it are numerous and diverse. It is closely associated with various elements such as age, income, years of training, sleep quality, anxiety, and depression. Therefore, it is recommended to implement appropriate measures to mitigate the occurrence of job burnout and enhance the quality of standardized training for residents. Such measures may include formulating reasonable training policies and theoretical learning plans, as well as providing mental health interventions.